The Prevalence and Overlap of Interstitial Cystitis/Bladder Pain Syndrome and Chronic Prostatitis/Chronic Pelvic Pain Syndrome in Men; Results of the RAND Interstitial Cystitis Epidemiology (RICE) Male Study - Suskind, Anne M. (2012)
PURPOSE: As part of the RICE study, we previously developed validated case definitions to identify interstitial cystitis/bladder pain syndrome (IC/BPS) in women and chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) in men. Using population-based screening methods, we applied these case definitions to determine the prevalence of these conditions in men. MATERIALS AND METHODS: A total of 6,072 households were contacted by phone to screen for men who had symptoms of IC/BPS or CP/CPPS. An initial 296 men screened positive, of which 149 met the inclusionary criteria and completed the telephone interview. For IC/BPS, two case definitions were applied (one with high sensitivity and one with high specificity), while for CP/CPPS, a single case definition (with both high sensitivity and specificity) was used. These case definitions were used to classify subjects into groups based on diagnosis. RESULTS: The IC/BPS weighted prevalence estimate for the high sensitivity and specificity definition was 4.2% (3.1-5.3%), and 1.9% (1.1-2.7%), respectively. The CP/CPPS weighted prevalence estimate was 1.8% (0.9-2.7%). These values equate to 1,986,972 (95% CI 966,042- 2,996,924) men with CP/CPPS and to 2,107,727 (95% CI 1,240,485 – 2,974,969) men with the high specificity definition of IC/BPS in the U.S.. The overlap between men who met either the high specificity IC/BPS case definition or the CP/CPPS case definition was 17%. CONCLUSIONS: Symptoms of IC/BPS and CP/CPPS are widespread among men in the US.. The prevalence of IC/BPS symptoms in men approaches that in women, suggesting that this condition may be underdiagnosed and undertreated in the male population.